Daily dynamics of photosynthesis of the freshwater red alga Sirodotia delicatula (Batrachospermales, Rhodophyta) - Kusakariba, Thiago [UNESP]; Necchi Junior, Orlando [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
P>The daily course of photosynthetic parameters of a population of the freshwater red alga Sirodotia delicatula from São Paulo State, Brazil (20 degrees 43'24 ' S, 49 degrees 18'21 ' W) was investigated under natural and laboratory conditions using dissolved oxygen and in vivo chlorophyll fluorescence techniques. Field specimens in laboratory conditions showed a defined daily pattern for net photosynthesis (NP) with two peaks observed in marine macroalgae and some freshwater red algae: the first (the highest) during the morning, and the second (the lowest and less evident) during the afternoon. Values of electron transport rate did not show a clear pattern of daily variation. NP results suggest the existence of an endogenous rhythm controlling photosynthesis. The study under natural conditions in two contrasting periods (autumn (June) and spring (October)) showed that the daily course of effective and potential quantum yield values was negatively correlated with irradiance and values were similar in the beginning and end of the day. These data evidenced, respectively, high excitement pressure on photosystem II and good recovery capacity (with lower values in spring) and a lack of irreversible photodamage to photosynthetic apparatus due to the prolonged exposure to high irradiances. Non-photochemical quenching values were also negatively correlated with the irradiance, suggesting a low dissipation capacity of excess energy absorbed by reaction centers. The results evidenced a typical pattern of daily variation with evident response to irradiance.
Keywords: chlorophyll fluorescence; daily variation; diurnal rhythm; Photosynthesis